Financial systems and economic growth : - Rousseau, Peter L.; Wachtel, Paul (Studies in macroeconomic history)
"An important literature on comparative long-run economic growth focuses on financial development. This work in economic history strongly complements the extensive empirical research by King and Levine (1993) and many others who have established a strong connection between financial development and subsequent economic growth. Rousseau and Sylla (2003) develop the concept of financial revolutions. They argue based on the history of the Netherlands, Great Britain, the United States, France, Germany and Japan, that these countries grew rapidly after financial revolutions which created "good" financial systems. Such systems have five key components: sound public finance and public debt management; a stable monetary regime; a banking system; a central bank; and well- functioning securities markets"--